2006
DOI: 10.1002/mds.20734
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and clinical characteristics of restless legs syndrome in Japanese patients with Parkinson's disease

Abstract: To explore the clinical significance of restless legs syndrome (RLS) in Parkinson's disease (PD) and the causal relationship between these two disorders, we made a comparison of both the prevalence of RLS and the severity of sleep disturbance manifested on the Pittsburg Sleep Quality Index (PSQI) between patients with PD (n=165) and age- and sex-matched control subjects (n=131). The prevalence of RLS diagnosed by clinical interview was significantly higher in PD patients than in control subjects (12% vs. 2.3%)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
101
4

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(118 citation statements)
references
References 23 publications
13
101
4
Order By: Relevance
“…Ondo et al 13 and Gomez et al 14 had found prevalence rates of 20.8% and 21.9%, respectively. Although, Nomura et al 15 and Krishnan et al 16 were not able to replicate these findings in their series of PD patients estimating prevalence rates of 12% and 7.9%, respectively. The higher prevalence noted among our group of PD patients may corroborate for the hypotheses of similar pathology between RLS and PD.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Ondo et al 13 and Gomez et al 14 had found prevalence rates of 20.8% and 21.9%, respectively. Although, Nomura et al 15 and Krishnan et al 16 were not able to replicate these findings in their series of PD patients estimating prevalence rates of 12% and 7.9%, respectively. The higher prevalence noted among our group of PD patients may corroborate for the hypotheses of similar pathology between RLS and PD.…”
Section: Discussionmentioning
confidence: 86%
“…In an Indian survey 16 , they reported a significant difference of mean age between PD patients with and without RLS (positive RLS: 63.70±7.8 years; negative RLS: 57.37±10.04 years; p=0.05). Nomura and associates 15 , however, concluded that PD patients without RLS seemed to be younger that those with RLS (positive RLS: 59.7±2.7 years; negative RLS: 70.1±0.8 years; p=0.0001).…”
Section: Discussionmentioning
confidence: 94%
“…This is in accord with other studies and confirms that the vast majority of PD patients develop RLS after onset of PD and most likely after the start of dopaminergic treatment. 4,24,25 Further hypotheses on RLS in PD include the effects of chronic dopaminergic medication. Angelini et al, 26 using data published by Salas et al, 27 suggested that PD, owing to its deficient dopaminergic neurotransmission, could also involve the A11 dopaminergic diencephalon-spinal pathway and thus represent a predisposing condition.…”
Section: Discussionmentioning
confidence: 99%
“…The RLS frequency for IPD patients in the present study was 10.0%, which is lower than the 20.8% reported by Ondo et al, 28 and closer to the 12% prevalence rate reported for Japan. 29 Ondo et al 28 reported that PD might be a risk factor for RLS and that a secondary RLS could occur after the onset of PD. Our results indicate that RLS is not necessarily associated with the Lewy body pathology that corresponds to PAF.…”
Section: Discussionmentioning
confidence: 99%